Author Correction: Evidence of Weak Anderson Localization Revealed by the Resistivity, Transverse Magnetoresistance and Hall Effect Measured on Thin Cu Films Deposited on Mica (Scientific Reports, 2021 11 1 17820 10.1038/S41598-021-97210-W) - Oyarzun-Medina, S (Nature Research, 2021)
Te original version of this Article omitted the Acknowledgements section. Te Acknowledgements section now reads: “S.O. would like to thank the fnancial support from Basal CEDENNA AFB180001.” Te original Article has been corrected. © 2021, The Author(s).